ADJUSTED PEDAGOGY FOR TEACHING STATISTICS - Stojanovski, Elizabeth (PEOPLE: International Journal of Social Sciences, 2015)
Traditional styles of teaching used to dominate the classroom for teaching statistics courses at tertiary level. It is proposed that knowledge will more likely be effectively learnt if traditional styles of teaching are supplemented with strategies from the more recent constructivist learning theory. It has the potential to result in increased collaboration in the classroom. When combined with the teacher’s role being more of a facilitator, and use of real-world applications, it is proposed that this will result in a more effective setting to encourage motivation and interest in learning. In turn, this will potentially provide a greater opportunity for improved learning outcomes.